Photoimmunotherapy: A New Paradigm in Solid Tumor Immunotherapy. (4th April 2022) - Peng, Zheng; Lv, Xiaolan; Huang, Shigao
In recent years, the incidence of cancer has been increasing worldwide. Conventional cancer treatments include surgery, chemotherapy, and radiation, which mostly kill tumor cells at the expense of normal and immune cells. Although immunotherapy is an accurate, rapid, efficient tumor immune treatment, it causes serious adverse reactions, such as cytokine release syndrome (CRS) and neurotoxicity. Therefore, there is an urgent need to develop an effective and nontoxic procedure for immunotherapy. The clinical combination of phototherapy and immunoadjuvant therapy can induce immunogenic cell death and enhance antigen presentation synergy. It also causes a systemic antitumor immune response to manage residual tumors and distant metastases. Photoimmunotherapy (PIT) is a tumor treatment combining phototherapy with immunotherapy based on injecting a conjugate photosensitizer (IR700) and a monoclonal antibody (mAb) to target an expressed antigen on the tumor surface. This combination can enhance the immune response ability, thus having a good effect on the treatment of residual tumor and metastatic cancer. In this review, we summarize the recent progress in photoimmunotherapy, including photoimmunoconjugate (PIC), the activation mechanism of immunogenic cell death (ICD), the combination therapy model, opportunities and prospects. Specifically, we aim to provide a promising clinical therapy for solid tumor clinical transformation.